2010
DOI: 10.1007/jhep06(2010)099
|View full text |Cite
|
Sign up to set email alerts
|

Causality in AdS/CFT and Lovelock theory

Abstract: Abstract:We explore the constraints imposed on higher curvature corrections of the Lovelock type due to causality restrictions in the boundary of asymptotically AdS spacetime. In the framework of AdS/CFT, this is related to positivity of the energy constraints that arise in conformal collider physics. We present explicit analytic results that fully address these issues for cubic Lovelock gravity in arbitrary dimensions and give the formal analytic results that comprehend general Lovelock theory. The computatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
174
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(187 citation statements)
references
References 54 publications
(179 reference statements)
11
174
1
1
Order By: Relevance
“…(5.11) This is the expected result for cubic Lovelock theory [62][63][64][65] where 2c 7 =c 8 and hence t 4 = 0. We have also checked that our general expressions are in agreement with [25,26,67,68].…”
Section: Jhep07(2014)098supporting
confidence: 53%
See 1 more Smart Citation
“…(5.11) This is the expected result for cubic Lovelock theory [62][63][64][65] where 2c 7 =c 8 and hence t 4 = 0. We have also checked that our general expressions are in agreement with [25,26,67,68].…”
Section: Jhep07(2014)098supporting
confidence: 53%
“…Direct holographic calculation of the three point functions are involved and challenging. We will follow the alternative route to derivation of the three point functions following the analysis of [23] and used in [23,25,26,[62][63][64][65]. The energy flux associated with a localized perturbation of fixed energy ij T ij , where ij is the polarization tensor, in the d(> 3) dimensional CFT background is given by…”
Section: Jhep07(2014)098 5 Three Point Functionsmentioning
confidence: 99%
“…Interesting implications of these terms within the context of the AdS/CFT correspondence has been recently the focus of thorough investigation (see, e.g., [8][9][10][11][12][13][14][15][16]). They allow for the holographic description of a broad family of quantum field theories (like 4d superconformal field theories with unequal central charges [17]), as well as for the study of the fluid/gravity correspondence beyond the EH gravitational sector.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this value is once conjectured as an universal lower bound for all materials [21][22][23][24][25][26][27][28][29]. However, the later study showed that the higher derivative gravity such as Gauss-Bonnet(GB) gravity can modify the lower bound to a lower value [15,[30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…And the case dual to general LoveLock gravity can give further modification to this lower bound [36,37].…”
Section: Introductionmentioning
confidence: 99%